Bridge transition monitoring: Interpretation of track defects using digital image correlation and distributed fiber optic strain sensing. (July 2020) - Pannese, Eric M; Take, W Andy; Hoult, Neil A; Yan, Ruobing; Le, Hoat
Railway bridge transitions represent locations of vertical stiffness variations that are believed to amplify the dynamic wheel loads which contribute to the development of both differential track settlement and hanging sleeper issues that are difficult to resolve despite the current knowledge of bridge transition behaviour. This paper presents a field monitoring study of a railway bridge transition in which track defects – including both gaps between the rail and sleeper plates, i.e. "rail–sleeper gaps, " and rail flange scrape marks exposing bare steel – were observed during a visual inspection of the transition. Trains were monitored by measuring both track displacements using Digital Image Correlation and distributed rail strains using a Rayleigh-based fiber optic analyzer. Through analysis and interpretation of the collected monitoring data, it was found that measurements of rail–sleeper gaps could be used to obtain a first-order estimate of the shape of the differential track settlement profile. Additionally, it was found that measurements of scrape marks on the rail flange could be used to estimate the extent of longitudinal rail movement that could occur during train passage, and that the loads applied to the bridge structure were influenced by the nature of the rail–sleeper gaps at the monitoring site.